Kelayakan Kopi Robusta Dan Tawas Sebagai Bahan Dasar Deodorant Stick - Netasya, Ajeng Bunga; Agustin, Eny Widhia (Jurnal Farmasi & Sains Indonesia, 2023)
Body odor is the decomposition of sweat compounds into acid compounds that cause odor. Body odor can be treated with deodorant cosmetics. Using deodorant triggers changes in underarm color because the alcohol content causes irritation. Research objectives 1) To determine the validity of deodorant products made from robusta coffee. 2) alum and to determine the suitability of deodorant products made from robusta coffee and alum. Data collection methods are observation, documentation, questionnaires and descriptive percentage analysis using lab tests, organoleptic tests, product validity, clinical tests and preference tests. The research results of the pH 5.78 lab test, positive vitamin C lab test, 83% organoleptic test, 82% product validation, 100% irritation clinical test, 3.5% panelist skin color level clinical test, 4% respondents, 91.6% anti-body odor clinical test, and 80% favorability test. In conclusion, product validation was declared valid, product suitability was declared suitable in organoleptic tests, lab tests, liking tests, clinical tests for irritation and body odor, and not suitable for clinical tests on skin color level. Suggestions for adding more effective ingredients by developing existing materials around and made in the form of a spray.